The Intersection of Education and Local Environmental Issues: Secondary Students' Views and Actions on Peatland Ecosystems in Global Warming Phenomenon - Kurdiati, Lintang Auliya; Fathurohman, Apit; Susiloningsih, Esti (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2024)
The escalating degradation of peatland ecosystems, coupled with the urgent global warming crisis, has raised concerns about the role of education in fostering environmental awareness and actionable solutions among younger generations. This study explores secondary students' views and actions regarding peatland ecosystems within the context of global warming. The purpose is to examine how education influences students' understanding of peatlands' role in climate change and the actions they take to mitigate environmental impacts. Using a mixed-methods design, semi-structured interviews and surveys were conducted with 105 students from grades 10 to 12 in Indonesia. Findings reveal that while students possess a strong awareness of peatlands' importance, their actions toward conservation remain limited. Many students express concern about global warming and peatland degradation but face barriers such as insufficient local initiatives and a lack of actionable knowledge. The study concludes that while education fosters awareness, there is a need for more practical, community-based learning opportunities to bridge the gap between knowledge and action. Implications suggest that integrating environmental education with hands-on conservation projects, as well as promoting stronger governmental and community involvement, could enhance student engagement in peatland conservation and other local environmental issues.